Tensile strength evaluation of glass/jute fibers reinforced composites: An experimental and numerical approach - Muhammad Yasir Khalid (17052429) (2021)
Polymer-based composites have an exceptional perspective to replace traditional structural materials like steel and aluminium, owing to their low weight, high strength, and outstanding performance at elevated temperatures. However, the utilization of natural reinforcements for functional polymer composites is still in infancy. In this study, the tensile properties of natural and synthetic fiber-reinforced hybrid composites are reported. Glass-jute hybrid composites, prepared through hand layup technique, were used with different glass and jute fiber stacking sequences. The experimental results stipulate that the tensile properties of glass fiber reinforced polymer (GFRP) were merely affected at lower jute fiber concentration. The strength of composites consisting of single jute fabric lamina and four glass-fiber laminas were comparable with five-laminas GFRP composites. For validation of the experimental tensile testing results, a numerical simulation was also executed. Errors between experimental and numerical simulations were found for different stacking sequences due to non-uniformity in jute fiber diameter and the manufacturing process adopted for these hybrid composites. Fractographic analysis revealed the micro voids and adhesive failure at different joining layers of fibers as the primary cause of delamination. Other Information Published in: Results in Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rineng.2021.100232